A Multicenter, Prospective, Observational, Cohort-Controlled Study of Clinical Outcomes Following Coronavirus Disease 2019 (COVID-19) Convalescent Plasma Therapy in Hospitalized Patients With COVID-19. (21st September 2021) - Chauhan, Lakshmi; Pattee, Jack; Ford, Joshay; Thomas, Chris; Lesteberg, Kelsey; Richards, Eric; Bernas, Carl A; Loi, Michele; Dumont, Larry; Annen, Kyle; Berg, Mary; Zirbes, Mercedes; et al.
Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has caused high inpatient mortality and morbidity throughout the world. COVID-19 convalescent plasma (CCP) has been utilized as a potential therapy for patients hospitalized with coronavirus disease 2019 (COVID-19) pneumonia. This study evaluated the outcomes of hospitalized patients with COVID-19 treated with CCP in a prospective, observational, multicenter trial. Methods: From April through August 2020, hospitalized patients with COVID-19 at 16 participating hospitals in Colorado were enrolled and treated with CCP and compared with hospitalized patients with COVID-19 who were not treated with convalescent plasma. Plasma antibody levels were determined following the trial, given that antibody tests were not approved at the initiation of the trial. CCP-treated and untreated hospitalized patients with COVID-19 were matched using propensity scores followed by analysis for length of hospitalization and inpatient mortality. Results: A total of 542 hospitalized patients with COVID-19 were enrolled at 16 hospitals across the region. A total of 468 hospitalized patients with COVID-19 were entered into propensity score matching with 188 patients matched for analysis in the CCP-treatment and control arms. Fine-Gray models revealed increased length of hospital stay in CCP-treated patients and no change in inpatient mortality compared with controls. In subgroup analysis of CCP-treated patients within 7 days of admission, there was no difference in length of hospitalization and inpatient mortality. Conclusions: These data show that treatment of hospitalized patients with COVID-19 treated with CCP did not significantly improve patient hospitalization length of stay or inpatient mortality. Abstract : A multicenter, prospective, cohort-controlled trial of COVID-19 convalescent plasma therapy in hospitalized patients with COVID-19 did not show benefit in time to discharge or inpatient mortality.